PENINGKATAN KEMAMPUAN LITERASI DAN NUMERASI SISWA SEKOLAH DASAR NEGERI JARAK - Ika, Yasinta Embu; Sumarding, Maksimus Nardi; Noge, Maria Desidaria (Mitra Mahajana: Jurnal Pengabdian Masyarakat, 2025)
This Campus Teaching activity was based on students' low Literacy and Numeracy skills at SDN Jarak, West Manggarai Regency, Komodo District. This activity aims to improve students' Literacy and Numeracy skills. The campus teaching activities include literacy and numeracy activities and technology adaptation. Based on this, the purpose of the study was to see the development of literacy and numeracy skills of students in grades 1-5 at a Jarak State Elementary School, which has its obstacles and challenges in improving literacy and numeracy skills. The research method used is descriptive qualitative. The results of the study showed that grade 5 students were very interested in learning that used learning media and learning methods carried out in groups, making learning very effective so that the development of Literacy and numeracy skills increased.